Increased growth in broad money after the outbreak of Covid-19 - Ragna Alstadheim (Norges Bank, 2022)
Growth in deposits and broad money aggregates surged in Norway after the outbreak of the Covid-19 pandemic. Usually, we think of deposit (or money) growth as going hand in hand with bank lending growth, since only banks can create money. But lending did not grow much more than usual in this period. Instead, high money growth was possible because domestic deposits replaced some of banks' net foreign funding. Higher financial savings and portfolio adjustments allowed deposit funding to replace some of the net foreign borrowing by banks, but also other factors contributed to money growth.
hdl:11250/3042515
Keywords: 330; Geldmenge; Coronavirus; Norwegen